Distinct Effects of Rac1 on Differentiation of Primary Avian Myoblasts - Gallo, Rita (The American Society for Cell Biology, 1999)
Rho family GTPases have been implicated in the regulation of the actin cytoskeleton in response to extracellular cues and in the transduction of signals from the membrane to the nucleus. Their role in development and cell differentiation, however, is little understood. Here we show that the transient expression of constitutively active Rac1 and Cdc42 in unestablished avian myoblasts is sufficient to cause inhibition of myogenin expression and block of the transition to the myocyte compartment, whereas activated RhoA affects myogenic differentiation only marginally. Activation of c-Jun N-terminal kinase (JNK) appears not to be essential for block of differentiation because, although Rac1 and Cdc42 GTPases modestly activate JNK in quail myoblasts, a Rac1 mutant defective for JNK activation can still inhibit myogenic differentiation. Stable expression of active Rac1, attained by infection with a recombinant retrovirus, is permissive for terminal differentiation, but the resulting myotubes accumulate severely reduced levels of muscle-specific proteins. This inhibition is the consequence of posttranscriptional events and suggests the presence of a novel level of regulation of myogenesis. We also show that myotubes expressing constitutively active Rac1 fail to assemble ordered sarcomeres. Conversely, a dominant-negative Rac1 variant accelerates sarcomere maturation and inhibits v-Src–induced selective disassembly of I-Z-I complexes. Collectively, our findings provide a role for Rac1 during skeletal muscle differentiation and strongly suggest that Rac1 is required downstream of v-Src in the signaling pathways responsible for the dismantling of tissue-specific supramolecular structures.